RUANG LINGKUP DOKUMEN APOSTILLE (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2022)
Ease of doing business as a major theme in economic development requires encouragement from various aspects of administrative procedures, one of which is the abolition of the legalization requirements for foreign public documents. The practice of legalizing foreign public documents or public documents to be used abroad, even though they have used an application, still requires a lot of time and money. In addition, another obstacle in the use of public documents is that public documents that have been legalized by institutions or ministries in Indonesia are not automatically accepted, but must go through a re-legislation process in accordance with the formal procedures of the destination country. The Apostille Convention was created to address this problem. With this convention, the formal procedure for legalization will be simplified, in addition to public documents that have been completed with apostille will be accepted by the treaty member countries. This study uses a normative juridical research method with secondary data. Data were analyzed by qualitative analysis method. Furthermore, the analysis also includes various scientific articles on apostille to add insight and understanding about apostille Keywords: apostille convention, Indonesia, public document. Abstrak Kemudahan berusaha sebagai sebuah tema besar dalam pembangunan perekonomian membutuhkan dorongan dari berbagai aspek prosedur administrasi, salah satunya adalah penghapusan syarat legalisasi dokumen publik asing. Praktik legalisasi dokumen publik asing atau dokumen publik yang akan digunakan di luar negeri, meskipun telah menggunakan aplikasi tetapi masih membutuhkan banyak waktu dan biaya. Selain itu, kendala lainnya dalam penggunaan dokumen publik adalah bahwa dokumen publik yang telah dilegalisir oleh lembaga atau kementerian di Indonesia tidak serta merta dapat diterima, melainkan harus melalui proses legislasi kembali sesuai dengan prosedur formal dari negara yang dituju. Konvensi Apostille dibentuk untuk mengatasi permasalahan ini. Dengan adanya konvensi ini maka prosedur formal legalisasi akan disederhanakan, selain itu dokumen publik yang telah dilengkapi apostille akan diterima oleh negara-negara anggota perjanjian. Penelitian ini menggunakan metode penelitian yuridis normatif dengan data sekunder. Data dianalisis dengan metode analisis kualitatif. Selanjutnya, analisis juga mencakup berbagai artikel ilmiah tentang apostille untuk menambah wawasan dan pemahaman tentang apostille.